Endometrial carcinoma in Kenya: clinical and biomarker profiles of 123 cases seen at two tertiary referral centers - Chesikaw, Olivia; Njau, Allan; Chesori, Erick; Warfa, Khadija; Mburu, Anisa; Shaffi, Afrin Fatima; Banet, Natalie; Wawire, Jonathan (Frontiers in Medicine, 2025)
IntroductionEndometrial carcinoma (EC) is the second-most common gynecologic malignancy globally after cervical cancer, with varying incidence and outcomes across different populations. It comprises a heterogeneous group of tumors with distinct histopathologic and molecular characteristics. This study aims to provide a comprehensive clinicopathologic characterization of EC in the Kenyan population, focusing on histologic types and immunohistochemical biomarker expression.MethodsThis retrospective study was conducted on archival tissue blocks from 123 patients diagnosed with EC at two major referral hospitals in Kenya. A tissue microarray block was constructed, and immunohistochemistry for 11 biomarkers, including ER, PR, p16, p53, NapsinA, ARID1A, PTEN, and Mismatch repair (MMR) proteins, was performed. Data analysis included descriptive statistics with Fisher’s exact test performed to compare proportions, while differences in means were compared using the Mann–Whitney U-test, with p < 0.05 considered significant.ResultsThe median age at diagnosis was 63 years, with the most common histologic type being endometrioid carcinoma (55.2%), followed by serous carcinoma (26%). Most low FIGO-stage patients had low-grade endometrioid histology. Obesity was the most frequently reported risk factor. Though hormone receptor biomarkers and p16 showed heterogeneous staining across all histologic types, ER and PR showed more frequent strong expression associated with endometrioid histology, while strong diffuse p16 staining was observed more frequently in serous carcinoma. MMR protein loss was predominantly observed in endometrioid carcinoma (30.0%), while all cases of serous carcinoma showed aberrant p53 expression. Abnormal p53 expression was also observed in 53.5% of all ECs, pointing to a higher percentage of patients with poor prognostic factors.DiscussionThis study provides a comprehensive clinicopathologic and immunophenotypic profile of EC in a Kenyan population. The predominance of endometrioid carcinoma and the frequent loss of MMR proteins in this subgroup align with global trends. However, the high proportion of p53-abnormal tumors, particularly among serous carcinomas, suggests a significant presence of biologically aggressive disease. These findings highlight the utility of IHC as a practical and informative tool for subtype classification and risk stratification in resource-limited settings.